HUBUNGAN PENGETAHUAN ORANG TUA TENTANG KESEHATAN SEKSUAL PADA ANAK USIA 7-12 TAHUN DENGAN SIKAP ORANG TUA DALAM PENCEGAHAN KEKERASAN SEKSUAL - Santy ' Fisnawati; Ganis ' Indriati; Veny Elita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This research is about the relationship of parent’s knowledge about sexual health of children 7-12 years with the attitudes of parent’s in prevention of sexual abuse was conducted in 5 public elementary school in Sukajadi District Pekanbaru with 369 parent’s as respondents. The purpose of this research was to determine the relationship of parent’s knowledge about sexual health of children 7-12 years with the attitudes of parent’s in prevention of sexual abuse. This research was descriptive correlation research with cross sectional approach. The samples were taken used cluster sampling technique. The data taken by questionnaire that has been composed by researcher that already tested for validity and reliability. The analysis used chi-square test. The results showed a relationship between parent’s knowledge about sexual health of children 7-12 years with  the attitudes of parent’s in prevention of sexual abuse (p value 0,043 < α 0,05). This research recommends to health workers to keep conduct health promotion for increase parent’s knowledge about sexual health to prevent child sexual abuse. Keywoard: Attitude, knowledge, sexual abuse, sexual health